Extending water vapor trend observations over Boulder into the tropopause region: Trend uncertainties and resulting radiative forcing. Issue 19 (1st October 2013) - Kunz, A.; Müller, R.; Homonnai, V.; M. Jánosi, I.; Hurst, D.; Rap, A.; M. Forster, P.; Rohrer, F.; Spelten, N.; Riese, M.
<x xml:space="preserve">Abstract</x> [1] Thirty years of balloon‐borne measurements over Boulder (40°N, 105°W) are used to investigate the water vapor trend in the tropopause region. This analysis extends previously published trends, usually focusing on altitudes greater than 16 km, to lower altitudes. Two new concepts are applied: (1) Trends are presented in a thermal tropopause (TP) relative coordinate system from −2 km below to 10 km above the TP, and (2) sonde profiles are selected according to TP height. Tropical (TPz>14km), extratropical (TPz<12km), and transitional air mass types (12km<TPz<14km) reveal three different water vapor reservoirs. The analysis based on these concepts reduces the dynamically induced water vapor variability at the TP and principally favors refined water vapor trend studies in the upper troposphere and lower stratosphere. Nonetheless, this study shows how uncertain trends are at altitudes −2 to +4 km around the TP. This uncertainty in turn has an influence on the uncertainty and interpretation of water vapor radiative effects at the TP, which are locally estimated for the 30 year period to be of uncertain sign. The much discussed decrease in water vapor at the beginning of 2001 is not detectable between −2 and 2 km around the TP. On lower stratospheric isentropes, the water vapor change at the beginning of 2001 is more intense for extratropical than for tropical air mass types. This suggests a possible link with changing dynamics above the jet stream such as changes in the shallow branch of the Brewer‐Dobson circulation.